Estimation of SLE Activity Based on the Serum Level of Chosen Cytokines and Superoxide Radical Generation - Elzbieta Waszczykowska; Ewa Robak; Anna Wozniacka; Joanna Narbutt; Jolanta Dorota Torzecka; Anna Sysa-Jedrzejowska (Mediators of Inflammation)
We estimated the serum levels of IL-6, TNF-α and IL10, and generation of superoxide radicals, as well as their mutual dependence, in 63 SLE patients at various stages of disease activity. Our results indicate a statistically significant increase of the serum levels studied, and an increase of superoxide anion generation by granulocytes, in correlation with SLE activity. These results indicate that oxygen metabolism and the examined cytokines play an important role in pathogenesis of SLE. The assessment of these parameters can be useful in the estimation of disease activity.